The Relation Between Cervical Vertebral Body Morphology and Craniofacial Parameters in Normal and Deep Bite Patients - Khawla M.Awni; Hind T. Jarjees; Enas T. Muhseen (University of Mosul, College of Dentistry, 2015)
Aims: The aims of the present ﬆudy were to describe the morphology of the cervical column in adult patients with a skeletal deep and normal bite occlusion, the prevalence of these morphology within them and to analyse the associations between the morphology of the cervical column and craniofacial parameters. Materials and Methods: The sample of this ﬆudy composed of two groups, deep bite and normal over bite. The normal or control group composed of 50 adult subjects (25 males and 25 females) aged 18-25 years. The deep bite group composed of 59 adult subjects (20 males and 39 females) aged 18-25 years. Lateral cephalometric radiograph were taken for both normal and deep bite groups. We used 12 variables 11 angular and 1 linear measurements. The morphology of the cervical column was evaluated by visual inspection of the ﬁrﬆ ﬁve cervical vertebrae as they are normally seen in on a ﬆandardized lateral cephalometric radiograph. Results: In the skeletal deep bite group, 53.4 per cent had fusion of the cervical column and 23.2 per cent poﬆerior arch deﬁciency (partial cleft). The fusion always occurred between C2 and C3. In the normal over bite group, 12.9 per cent fusion of the cervical column and 5.35 per cent of poﬆerior arch deﬁciency, the fusion always occurred between C2 and C3. The signiﬁcant correlations were seen between fusion and the angle between palatal plane and mandibular plane, the angle formed between the long axis of upper central incisor and palatal plane and the diﬆance between the incisal edges of upper and lower central incisors, also the signiﬁcant correlation between poﬆerior arch deﬁciency and the angle between palatal plane and mandibular plane, the angle between the mandibular plane and chin line, gonial angle and the angle formed between the long axis of upper central incisor and palatal plane. Conclusions: The deep bite group had more deviations of the cervical column than the normal group. Our results showed that the craniofacial parameters, occlusion and malformations of the jaws were aﬀected by morphological deviations of the upper cervical vertebrae including fusion and poﬆerior arch deﬁciency.